Akan ethnomathematics: Demonstrating its pedagogical action on the teaching and learning of mensuration and geometry - Isaac Owusu-Darko (Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
The mathematics curriculum implementation depends largely on teachers’ choice of pedagogical skills that would influence meaningful teaching and learning. The suggestive ideal approach this paper presents is to consider exploration and demonstration of Akan (a tribe in Ghana, West Africa) ethnomathematics in the teaching and learning of some selected mensuration and geometrical concepts found in the secondary school curriculum. The study found various Akan ethnomathematical processes supporting the teaching and learning of school geometrical and mensuration topics such as artefacts, buildings, tools, and among others. The ethnomathematical processes reveal a resemblance of pi () concepts and its application to ethno-technology from selected artefacts used for pedagogical demonstrations. We recommend further research into the practical effect of ethnomathematics move in teaching other mathematical concepts in several communities where there exists cultural diversity. It is suggested that mathematics educators adopt ethnomathematics methodology by integrating it into the curriculum implementation process to check its impact on the teaching and learning of mathematics.